Histological Structure of Anterior Cruciate Ligament - Review - Banu, Jahira; Sontakke, Yogesh; Tamgire, Dharmaraj; H Y, Suma (Academia Anatomica International, 2019)
Introduction: Anterior cruciate ligament (ACL) is one of the commonly injured ligaments of the knee joint due to sports activities. Because of the poor healing capacity of the ACL, surgical treatment for ACL injuries was followed for many years. Therefore, understanding the structural knowledge of the ACL will help in reproduce the native ACL. Objectives: To improve the histological knowledge of ACL and to understand the valuation of histology of ACL attachment to the bone. Subjects and Methods: PubMed and Google search was used as a search engine to collect the concerned articles that describing the histology of ACL. The key words were ACL, histology, Ultrastructure. Results: Ultrastructure of ACL observed from proximal to distal attachments showed the more complicated and complex arrangement of collagen bundles with interspersed cells in between. Ultrastructure of ACL also should be borne in mind before preparing ACL grafts. Conclusion: ACL has complex histological structure. It is essential to consider the details of the ACL histological structure in ACL reconstruction surgeries to restore its full functionality. This review may be useful as a reference to investigate the mechanical properties of ACL footprint.